Change in White Male Rats’ Weight and Epididimic Histology Due to the Provision of White Turmeric Extract and Fraction - Rinda Lamdayani; Aryanti Aryanti (GLOBAL HEALTH SCIENCE GROUP, 2021)
The low participation of Men in the family planning program is due to the limited choice of male contraceptives that can be used. This makes experts trying to find a way that is safe for men, one way is to switch plants that can inhibit the spermatogenesis. One of the traditional medicines that has been studied and has anti-fertility effectiveness is the white turmeric plant. This study aimed to determine the effect of extracts and fraction of white turmeric on changes in weight and histology of white male rats (Rattus norvegicus) epididymis. This research was an experimental study using a completely randomized design (CRD). The samples in this study were 25 white male rats that met the inclusion criteria which were divided into 5 groups, each group consisting of 5 rats obtaining a dose of 300 mg/kgBW/day, treated for 48 days and stopped for surgery on the day 49. After that, the analysis was carried out using One Way Anova test and continued with Duncan's test. The provisions of extracts and fractions of white turmeric can reduce the weight and histological structure of the epididymis of the head, corpus, and cauda.